Pengendalian Kendaraan Bermotor Jenis Angkutan Kota (Studi Kasus Tentang Uji Berkala Kendaraan Bermotor Pada Dinas Perhubungan Kabupaten Bandung) - Anzani, Elvira Aprilla (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
This research is motivated by the non-optimal testing of Motorized Vehicle types of city transportation in the Department of Transportation of Bandung Regency, from the background of the problem the researcher identifies the problem, namely: How to control the periodic testing of motorized vehicles of city transportation types in Bandung Regency, What are the factors that support and inhibit the control periodic testing of motorized vehicles of urban transportation in Bandung Regency. And what efforts are made by the Bandung Regency Transportation Agency in controlling periodic motorized vehicle testing. The foundation of this theory uses the Control theory, the researchers formulate the proposition as follows: Periodic Control Tests of Motorized Vehicles in City Transport Types In Bandung Regency will run optimally if it pays attention to through control processes that consist of determining standards to be used in control, measuring implementation or the results achieved, measure implementation or results with standards and determine deviations if any and take corrective action. The results of this study indicate that the control of motorized vehicles of city transportation in Bandung Regency based on Bandung Regency Regulation No. 9 of 2012 concerning Operation of Traffic and Road Transportation, there are several supporting factors and inhibiting factors. To overcome the obstacle, one of the efforts made by the Department of Transportation in collaboration with the Police is the disappearance of violators.